KnowledgeBoat Logo

Mathematics

Without using trigonometric tables, prove that:

cot 54°tan 36°+tan 20°cot 70°2=0\dfrac{\text{cot 54°}}{\text{tan 36°}} + \dfrac{\text{tan 20°}}{\text{cot 70°}} - 2 = 0

Trigonometrical Ratios

6 Likes

Answer

To prove,

cot 54°tan 36°+tan 20°cot 70°2=0\dfrac{\text{cot 54°}}{\text{tan 36°}} + \dfrac{\text{tan 20°}}{\text{cot 70°}} - 2 = 0.

Solving, L.H.S. of the equation we get :

cot 54°tan 36°+tan 20°cot 70°2cot (90° - 36°)tan 36°+tan 20°cot (90° - 20°)2tan 36°tan 36°+tan 20°tan 20°21+120.\Rightarrow \dfrac{\text{cot 54°}}{\text{tan 36°}} + \dfrac{\text{tan 20°}}{\text{cot 70°}} - 2 \\[1em] \Rightarrow \dfrac{\text{cot (90° - 36°)}}{\text{tan 36°}} + \dfrac{\text{tan 20°}}{\text{cot (90° - 20°)}} - 2 \\[1em] \Rightarrow \dfrac{\text{tan 36°}}{\text{tan 36°}} + \dfrac{\text{tan 20°}}{\text{tan 20°}} - 2 \\[1em] \Rightarrow 1 + 1 - 2 \\[1em] \Rightarrow 0.

Since, L.H.S. = R.H.S.

Hence, proved that cot 54°tan 36°+tan 20°cot 70°2=0\dfrac{\text{cot 54°}}{\text{tan 36°}} + \dfrac{\text{tan 20°}}{\text{cot 70°}} - 2 = 0.

Answered By

3 Likes


Related Questions